Knitting the Chain of Anti-Colonialism: Kiai and Pesantren's Political Activities in Berbek from the Late 1800s to the Early 1900s - Ilyas, Ilyas; Maryani, Lesi; Wahyudhi, Johan; Zamani, Muhammad Zaqi Al (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This paper explores the role and political activities of kiai and pesantren in Berbek (present-day Nganjuk) during the late 19th and early 20th centuries in the context of resistance to Dutch colonialism. Through a social and political history approach, this study explores how kiai and pesantren became the centre of the anti-colonial movement, spread ideas of freedom, and shaped nationalist identity in Berbek society. The results provide deep insights into how the anti-colonial movement developed and forged a strong network in an effort to achieve national independence.